Meningkatkan Creativepreneurship pada Siswa SMKN 4 Kabupaten Tangerang - Cahyani Kurniastuti; Ismayudin Yuliyzar; Priyo Susilo; Resy Perwithasari (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Dedication to the Society with the theme Increasing Creativepreneurship in Students at SMKN 4 Tangerang Regency "is a real effort to increase students' ability to create entrepreneurship with a creative approach and following technological developments". Anyone can become a creativepreneur as long as they can create and promote products in a way that is creative, unique, interesting and follows current trends in society. Of course, becoming a creativepreneur is not easy because it requires hard work, commitment and continuous effort as well as following technological developments and trends in society in order to build a successful business. The stages of this community service activity are carried out with the Preliminary Study preparation stage, Preparation of Goals and Targets, Socialization and Registration, Development of Educational Materials including the importance of creativity in entrepreneurship, types of creativepreneur activities, and the use of social media to promote business, Monitoring and Evaluation.